Feasibility of Thyroid Imaging Reporting and Data System Classification in Predicting Thyroid Malignancy. Issue 12 (December 2019) - Dural, Ahmet Cem; Sahbaz, Nuri Alper; Akarsu, Cevher; Akbulut, Sezer; Turkay, Rustu; Baytekin, Halil Firat; Alis, Halil
In this study, we aimed to evaluate the diagnostic value of thyroid imaging reporting and data system (TIRADS) in the estimation of malignancy and assess the concordance between TIRADS and the histopathology results of the postoperative specimens. Consecutive ultrasound imaging records of patients with multinodular goiter from January 2010 to December 2017 who underwent surgery were retrospectively reviewed. The risk of malignancy of each TIRADS category was determined, and correlation with pathology was assessed. The patients with malignant cytology findings (Bethesda 6) who were categorized TIRADS 6 were excluded from the study. The positive and negative predictive values, sensitivity, specificity, and accuracy of the TIRADS classification were calculated on a 2 x 2 table with their own formulas. A total of 1457 patients were evaluated, and 1122 of these were included in the study. The risk of malignancy for nodules evaluated as TIRADS 2 was 0.6 per cent, TIRADS 3 was 13.1 per cent, TIRADS 4a was 20 per cent, TIRADS 4b was 61.1 per cent, TIRADS 4c was 85.7 per cent, and TIRADS 5 was 93.3 per cent. The positive predictive value of TIRADS classification was found to be 43.4 per cent, negative predictive value was found to be 90.7 per cent, sensitivity was found to be 78 per cent, specificity was found to be 68.4 per cent, and accuracy was found to be 70.7 per cent for our institution. The TIRADS classification based on suspicious ultrasound findings is reliable in predicting thyroid malignancy and can be routinely used in daily practice.